Policy design for territorial equity in multi‐level and multi‐sectoral political systems: Comparing health and education strategies. Issue 5 (21st September 2021) - Cairney, Paul; Kippin, Sean; St Denny, Emily; Mitchell, Heather
Abstract: The EU has many plans to foster equity and spatial justice. However, each has separate reference points, and it is difficult to find an overall vision. To demonstrate, we analyse two sectoral strategies to identify their implications for spatial justice strategies. Education focuses on early investment and public service reform. Health prioritises intersectoral action to address the 'social determinants' beyond the control of health services. Both warn against equating territorial cohesion or spatial justice with equal access to public services. These findings could inform European Commission strategy, but it tends to respond with renewed rhetoric rather than reconsidering its approach. Resumen: La UE tiene muchos planes para fomentar la equidad y la justicia espacial. Sin embargo, cada uno tiene puntos de referencia distintos, y es difícil encontrar una visión global. Para demostrarlo, este estudio analizó dos estrategias sectoriales para identificar sus implicaciones en las estrategias de justicia espacial. La educación se centra en la inversión temprana y la reforma de los servicios públicos. La salud prioriza las acciones intersectoriales para abordar los 'determinantes sociales' más allá del control de los servicios sanitarios. Ambos sectores advierten del peligro de equiparar la cohesión territorial o la justicia espacial con la igualdad de acceso a los servicios públicos. Estos hallazgos podrían informar la estrategia de la Comisión Europea, pero ésta tiende a responder con una retórica renovada en lugar de reconsiderar su enfoque. 抄録: EUには平等と空間的正義を促進する多くの計画がある。しかし、計画はそれぞれ基準点が異なり、全体像を捉えるのは困難である。そこで、2つのセクターのストラテジーを分析し、空間的正義のストラテジーに対する意義を確認して実証を試みた。教育セクターは、早期投資と公共サービスの改革に焦点を合わせている。保健医療セクターは、保健サービスの範囲を超えた「社会的決定要因」に対処するためにセクター間での行動を優先している。両者は、領土的結束 (Territorial Cohesion)や空間的正義と公共サービスへの平等なアクセスとを同一視することに対して警告を発している。以上の結果は欧州委員会のストラテジーに影響を与える可能性があるが、欧州委員会はアプローチを見直すのではなく、新たなレトリックを用いて対応する傾向がある。